Are cross-country studies of the Environmental Kuznets Curve misleading? New evidence frome time series data for Germany - Hannes Egli (Fondazione Eni Enrico Mattei (FEEM), 2002)
In recent years, extensive literature on the Environmental Kuznets Curve leading to optimistic policy conclusions has attracted great attention. However, the underlying cross-section estimations are not very reliable. Accordingly, this contribution uses time series data for a single country with good data quality: Germany. With a specification that includes all theoretical variations and different appropriate estimation procedures, it is found that only for few pollutants can the typical EKC pattern be confirmed. For the major part, however, it is concluded that the doubts about the suitability of the EKC approach are well-founded.
Keywords: Q00; Q20; Q25; 330; Environmental Kuznets Curve; time series data; error correction model; Umweltbelastung; Wirtschaftswachstum; Zeitreihenanalyse; Schätzung; Deutschland; Environmental Kuznets Curve; Fehlerkorrekturmodell